Chosen Antioxidant Enzymes GPx4 and GPx8 in Human Colorectal Carcinoma: Study of the Slovak Population - Andriana Pavliuk-Karachevtseva; Jozef Mihalik; Róbert Biel; Silvia Rybárová; Ingrid Hodorová (Medicina, 2022)
Background and Objectives: Nowadays colorectal carcinoma (CRC) is one of the most common causes of death in patients with malignant neoplasms worldwide. Our work aimed to determine the possible involvement of glutathione peroxidases 4 and 8 (GPx4 and GPx8) in this specific tumor process. Materials and Methods: The expression of GPx4 and GPx8 in 58 specimens of human colorectal cancer tissues and normal tissues was detected by the indirect immunohistochemical method under a light microscope. Statistical analysis was done by Chi-squared test. Histological findings were compared with data such as gender, age, tumor grade, histotype and lymph nodes alteration. Results: In all specimens of healthy tissue the presence of both, GPx4 and GPx8, was detected in the cytoplasm of epithelial cells. On the other hand, a positive immunohistochemical reaction against GPx4 only in 41.4% and against GPx8 only in 29.3% of human colorectal adenocarcinoma specimens were observed. Any significant difference between the presence of GPx and the age, the gender of the patient, tumor grade, histotype of cancer and the lesion of regional lymph nodes has not been detected. Conclusions: Our foundation could mean, that GPx4 and GPx8 have no important role in CRC pathogenesis, but the loss of these enzymes probably indicates a serious pathological process ongoing in the large intestine. To our knowledge, this is the first paper describing GPx8 presence in human colorectal carcinoma.